Comment: Lakoff on Metaphor – More Heat Than Light. (July 2016) - Goddard, Cliff
This comment questions the logic and evidence base of Lakoff's (2016) account of metaphor, embodiment, and the so-called neural theory of language. It calls for proper attention to linguistic and cultural diversity and opposes biophysical reductionism.